THE LEGALITY OF STATE’S PEACETIME MILITARY ACTIVITIES - Ramon, Adrianus Adityo Vito (Veritas et Justitia, 2017)
AbstractThe research argue that in the absence of an internationally negotiated provisions that explicitly regulate foreign peacetime military activities in the Exclusive Economic Zone (EEZ) of another States, States should consider the incident case per case as well as may employed the guideline prepared by highly reputed international legal scholars. This is essential to avoid unnecessary conflict between the Coastal State and the State conducting military activities in the EEZ. The aforementioned conclusion is reached by first analysing the definition of the peacetime military activities of the State. The research would also examine the negotiation process and its negotiated provisions of the United Nations Convention on the Law of the Sea (UNCLOS) 1982 resulted from the negotiation, regulating EEZ. Subsequently, the research would examining of the practice of the States interpreting the UNCLOS 1982’s EEZ provisions, including providing the options as an interim solutions for the void in the legal instruments in the matter.